UJI EFEK ANTIASKARIASIS EKSTRAK METANOL AKAR CEGUK (Quiqualis indica L) TERHADAP CACING (Ascaris lumbricoides var.suum) SECARA IN VITRO - Nurlina, Nurlina (Jurnal Ilmiah As-Syifaa, 2010)
An in vitro research on the antiascariasis effect of methanol extract of â€œcegukâ€ root againstÂ  Ascaris lumbricoides var. suum had been conducted. The aim of this research was study the antiascariasis effect of methanol extract of â€œcegukâ€ root against roundworm. This research used Ascaris lumbricoides var. suum which divided into five groups, three treatment groups were immersed in 5%, 15% and 25% w/v suspension concentration of methanol extract of â€œcegukâ€ root, one control group was immersed in 1% w/v Na CMC colloidal and one comparative group was immersedÂ  in 0,125% w/v suspension concentration of pyrantel pamoat and then were incubated at 37Â±0,5O C. the observation was done by counting the roundworm which was dead at 1st, 2nd, 3rd,4th, 5th, 6th, 12th, 18th, and 24th hours of observation. The result of observation was show all concentration methanol extract of â€œcegukâ€Â  root had antiascariasis effect. Antiascariasis effect of the comparative group of 0,125% w/v pyrantel pamoat faster than antiascariasis effect of 25% w/v methanol extract of â€œcegukâ€ root, which the comparative group showed the dead of roundworm 100% at 3rd, hour and the 25% w/v methanol extract showed the dead of roundworm 100% at 18th hour.Key words : ceguk root, antiascariasis